2015
DOI: 10.1007/978-3-319-24553-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Motor Function in Very Preterm Infants Using Connectome Features and Local Synthetic Instances

Abstract: Abstract. We propose a method to identify preterm infants at highest risk of adverse motor function (identified at 18 months of age) using connectome features from a diffusion tensor image (DTI) acquired shortly after birth. For each full-brain DTI, a connectome is constructed and network features are extracted. After further reducing the dimensionality of the feature vector via PCA, SVM is used to discriminate between normal and abnormal motor scores. We further introduce a novel method to produce realistic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…S1, online supporting information). Twenty‐six studies met the inclusion criteria and five further studies were identified by manual review of references of included papers . Demographic and clinical data extracted from the 31 studies included in this review are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1, online supporting information). Twenty‐six studies met the inclusion criteria and five further studies were identified by manual review of references of included papers . Demographic and clinical data extracted from the 31 studies included in this review are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies from nine distinct cohorts acquired early diffusion MRI data . Sensitivity and specificity of diffusion MRI findings to determine later motor outcomes and/or CP in individual studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundreds of studies have employed this definition in brain connectomics with the obvious limitation of “diluting” the connectome. The second approach restricted connectivity based on only the endpoints of each fiber such that a single fiber could connect at most two regions and that fiber is counted only once in the final connectome (two-region or endpoint fibers; Figure 3C) [17, 18, 19, 20]. Here, we hypothesized that using two-region (endpoint) fibers would be more informative by avoiding the “overcounting” of connections and focusing on real axonal pathways in the connectome.…”
Section: Methodsmentioning
confidence: 99%
“…As an example application, we used heat kernel features for classifying between preterm infants with normal and adverse motor function. MRI-based features such as white matter injury (WMI), intraventricular haemorrhaging (IVH) or diffusion MRI measures of white matter tract integrity from infants scanned near term-equivalent age have been shown to be associated with developmental outcome [69,49,70]. Brown et al classified preterm infants by motor score and showed that a combination of standard global network measures from diffusion tractography, WMI, IVH and GA achieved sensitivity, specificity and accuracy scores of 66, 79, 72.3%, respectively [70].…”
Section: Interpretation Of Heat Kernel Featuresmentioning
confidence: 99%